Benefits of Exergaming Regarding to Conventional Physical Therapies on Balance and Fall Risk in Prefrail and Frail Older People: A Meta-Analysis of Randomized Controlled Trials - Herrera-Valenzuela, T (SAGE PUBLICATIONS INC, 2025)
This systematic review and meta-analysis evaluated how exergaming (EXG) compares with various conventional physical therapies in improving balance and reducing fall risk among prefrail and frail older people. We searched 6 databases PubMed, Medline, CINAHL Complete, Scopus, the Cochrane Library, and Web of Science up to April 2025. Study quality and evidence certainty were appraised using PRISMA, TESTEX, Rob 2, and GRADE. For meta-analysis, Hedge s g effect sizes were computed for balance and fall risk outcomes. We chose fixed- or random-effects models and conducted subgroup analyses based on therapy dosage (sessions per week and minutes per session). The protocol is registered in PROSPERO (CRD420251009891). From 2434 records, 10 RCTs (n = 400; mean and standard deviation age 75.7 +/- 5.9 years) met inclusion criteria. Overall and subgroup meta-analyses (4 each) showed significant EXG benefits for the Mini-BESTest (P < .01), Timed Up-and-Go (TUG; P < .05) and Fall Efficacy Scale-International (FES-I; P < .05). No statistically significant change was found for the Berg Balance Scale (BBS; P = .05). When stratifying by dosage, EXG outperformed controls in TUG specifically for protocols with fewer than 3 sessions/week and under 50 min/session (P < .01). Dosage did not significantly influence FES-I outcomes. EXG is an alternative therapy that improves balance by reducing the fall risk, as measured by the Mini-BESTest, TUG, and FES-I, compared with conventional physical therapies (ie, physiotherapy, balance training, strength training, aerobic training, multicomponent training). Notably, protocols with <3 weekly sessions of <50 min each yielded the most pronounced TUG improvements.